2011 IEEE International Conference on Signal Processing, Communications and Computing (ICSPCC) 2011
DOI: 10.1109/icspcc.2011.6061807
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of mine sweeper's lake and sea test data using GM(1,2) model

Abstract: The conversion model of mine sweeper's lake and sea test data was set up by using the GM(1,2) model of the grey system theory. For the merit of the grey system, the problem of small samples can be solved. The results show that the method is easy, realistic, and has high conversion precision, which can be taken as good references.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Over the years, several studies regarding the practical usage of the GM(1, 2) model have been done, among them it can be mentioned: the usage of GM(1, 2) model for conversion of mine sweepers lake and sea test data (Cheng et al, 2011), electricity price forecasting (Wang, 2010;Wang et al, 2010), simulation of the runoff to climate change (Li et al, 2009), lag effect of productivity and GDP (Wu et al, 2007), decision making (Bai and Wang, 2005), etc. Also a review on the usage of the grey models in economics can be found in Delcea (2015a, b).…”
Section: Research Statusmentioning
confidence: 99%
“…Over the years, several studies regarding the practical usage of the GM(1, 2) model have been done, among them it can be mentioned: the usage of GM(1, 2) model for conversion of mine sweepers lake and sea test data (Cheng et al, 2011), electricity price forecasting (Wang, 2010;Wang et al, 2010), simulation of the runoff to climate change (Li et al, 2009), lag effect of productivity and GDP (Wu et al, 2007), decision making (Bai and Wang, 2005), etc. Also a review on the usage of the grey models in economics can be found in Delcea (2015a, b).…”
Section: Research Statusmentioning
confidence: 99%